Biomass and Nutrients Accumulation in Cryptomeria japonica Plantations of Darjeeling - , Bajrangsingh (Indian Forester, 1994)
Biomass and nutrient accumulation were studied for eight stands, ranging from seven to 40 years in age grown in the Darjeeling Hills. Aboveground biomass varied from 0.5 to 158.0 t/ha. The highest concentrations almost nutrients were found in the leaf. Nutrient concentrations of Ca (2.9 per cent) and N (2.3 per cent) were greatest and P (0.022 per cent) least. Nutrient accumulation and biomass increased with age of stand but their proportion in aerial components of plants were reversed (greater in young and less in mature stands). In early stages of stand development Ca was higher than N. The nutrient pool in standing crop biomass of the oldest stand was nearly 698 kg Ca 422 kg Mg, 863 kg K, 67 kg Na, 118kg N and55 ke P per hectare and their accumulation efficiency followed a similar pattern to that of biomass and nutrients with respect to stand age.